2017
DOI: 10.1016/j.afos.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover rate and bone formation/resorption balance during the early stage after switching from a bone resorption inhibitor to denosumab are predictive factors of bone mineral density change

Abstract: ObjectivesThis study aimed to investigate the correlation between bone mineral density (BMD) and the turnover rate [√(MoMf2 + MoMr2), multiple of median formation (MoMf) was calculated as bone-specific alkaline phosphatase (BAP) value/18.6 and multiple of median resorption (MoMr) as tartrate-resistant acid phosphatase 5b (TRACP-5b) value/463] and the balance (MoMf/MoMr) and to compare differences in therapeutic effects evoked by differences in previous treatments.MethodsIn 51 osteoporotic women treated with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…These markers would change more sensitively than BMD within the relatively shorter 6‐month period, which was observed in the present study 25 . In a previous study, the change in bone metabolic markers from SERM to Dmab showed a greater reduction than from BP to Dmab in the study population, including non‐type 2 diabetes mellitus patients 26 . Those results were consistent with the results of the present study in the population with type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These markers would change more sensitively than BMD within the relatively shorter 6‐month period, which was observed in the present study 25 . In a previous study, the change in bone metabolic markers from SERM to Dmab showed a greater reduction than from BP to Dmab in the study population, including non‐type 2 diabetes mellitus patients 26 . Those results were consistent with the results of the present study in the population with type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
“…BMD increases in response to Dmab were similar between responders and non-responders to previous BP treatment 17 . It was also shown that LS and FN BMD values increased significantly at weeks 24 and 48 compared with week 0 after switching from SERM to Dmab in 19 osteoporotic women 18 . Although Dmab is effective in patients with BP-and SERM-resistant primary osteoporosis 12,17 , there have been no reports on its effects in the type 2 diabetes mellitus population or the effects of switching from SERM to Dmab.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, denosumab had a greater effect on BMD gain if initiated after bisphosphonate treatment than after selective oestrogen receptor modulators, in spite of a lower bone turnover at treatment initiation in the former group. 134 To our knowledge, the effect baseline bone turnover on the efficacy of denosumab in advanced CKD has yet to be determined. However, a recent study, demonstrating a positive effect of denosumab on BMD in advanced CKD, used an upper limit for PTH of 240 pg/mL, thereby increasing the probability of selecting patients with bone turnover in the lower spectrum.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The balance between bone formation and resorption may have shifted to favour formation during this period. It has been reported that BMD increased when the predominantly formative state of bone was maintained 21 . In fact, S‐TRACP‐5b levels remained low compared with those at baseline, while S‐ALP levels recovered during that period (Figure 2f).…”
Section: Discussionmentioning
confidence: 74%
“…It has been reported that BMD increased when the predominantly formative state of bone was maintained. 21 In fact, S-TRACP-5b levels remained low compared with those at baseline, while S-ALP levels recovered during that period (Figure 2f). recovered after 12 months, when STx was terminated ( Figure 2F).…”
Section: Discussionmentioning
confidence: 85%